Contribution of vitamin D deficiency to the risk of coronary heart disease in subjects with essential hypertension. (January 2016) - Nargesi, Arash Aghajani; Heidari, Behnam; Esteghamati, Sadaf; Hafezi-Nejad, Nima; Sheikhbahaei, Sara; Pajouhi, Atieh; Nakhjavani, Manouchehr; Esteghamati, Alireza
Abstract: Background: Vitamin D deficiency is proposed as a risk factor for coronary heart disease (CHD). An inverse relation was observed between serum 25-Hydroxy-Vitamin-D level and incidence of hypertension. This study aimed to evaluate the predictive value of serum 25-Hydroxy-Vitamin-D in improvement of CHD risk-stratification in patients with hypertension. Methods: In this cohort, we followed 1586 patients with essential hypertension (1078 diabetic and 508 non-diabetic) for 8.5 years. Physician-adjudicated first hard CHD event was the primary outcome. Cox regression analysis was used to investigate the association between 25-Hydroxy-Vitamin-D quartiles and incident CHD. 25-Hydroxy-Vitamin-D was also added to the Framingham Risk Score (FRS) and Net-Reclassification-Improvement (NRI) and Integrated-Discriminant-Improvement (IDI) were used to examine improved reclassification. Results: During follow-up, 176 events were recorded. Patients in the lowest quartile of 25-Hydroxy-Vitamin-D experienced the most number of hard CHD events. A significant linear trend was observed in hazard ratios (HR) of incident hard CHD events in 25-Hydroxy-Vitamin-D quartiles which remained significant after multiple adjustments for conventional CHD risk-factors (HRs in full-adjusted model: 2.87 [1.76–4.70] for 1st quartile, 2.31 [1.39–3.83] for 2nd quartile and 1.87 [1.15–3.03] for 3rd quartile, compared with the highest quartile; p-for-trend<0.001). Addition of 25-Hydroxy-Vitamin-D to FRS could improve CHD risk-estimation (relative-IDI = 15%, p-value<0.001). Addition of 25-Hydroxy-Vitamin-D to FRS successfully reclassified 33% [18–49] of patients with hypertension among CHD risk groups (p-value<0.001). Conclusion: We observed that serum 25-Hydroxy-Vitamin-D is independently associated with future hard CHD events and improves its prediction in patients with essential hypertension. Addition of serum 25-Hydroxy-Vitamin-D to CHD risk-estimation models may have additive values.